Operational Effectiveness Evaluation of Antimissile Early Warning Based on Combination Weighted TOPSIS. Issue 1 (May 2021) - Qu, Shi; Zheng, Yi; Yan, Hua; Deng, Weiqiang; Liu, Taiyang
Abstract: Operational effectiveness evaluation is of great significance for early warning operation of antimissile, which provides quantitative basis for equipment development, operational planning, combat method research and operational management. In view of the shortcomings of TOPSIS, this paper improves the TOPSIS method. First, before calculating positive and negative ideal solutions, it establishes corresponding standardized methods for different evaluation indexes to solve the problems of inconsistent impact of each evaluation index on operational effectiveness and the "drowning" of small value indexes by large value indexes. Second, it calculates the weight of each index based on combination weighting method to overcome the shortcomings of single subjective or objective weighted method. On this basis, the operational effectiveness evaluation method of antimissile early warning based on combination weighted TOPSIS is proposed, and the quantitative evaluation and comparative analysis of different operational schemes are carried out. The simulation results show that the effectiveness evaluation result of antimissile early warning operation based on combination weighted TOPSIS method is scientific.